Rhoptry-neck Protein-2, a Novel Marker of Plasmodium vivax Liver Stage Schizont and Hypnozoite - Praikongkatham, Chonnipa; Niramolyanun, Gamolthip; Naktubtim, Chonnapat; Jiraungkoorskul, Wannee; Naranuntarat Jensen, Amornrat; Jenwithisuk, Rachaneeporn; Roobsoong, Wanlapa; Sattabongkot, Jetsumon; Kangwanrangsan, Niwat (Ramkhamhaeng Research Journal of Sciences and Technology, 2020)
Relapse is a serious problem caused by vivax malaria. The dormancy stage called hypnozoite can be latent in the hepatocyte for several weeks or years, waiting for reactivation before developing into liver stage schizont. The biology of hypnozoite is not well understood. Furthermore, the study of the liver stage of human malaria is also difficult, due to the lack of small laboratory animal models and the restriction of specific binding molecules between human malaria parasites and human host cells. Thus, the study of the hypnozoite marker would be beneficial for further study of hypnozoite biology and the relapse mechanism. Rhoptry Neck Protein-2 (RON-2), the well-known rhoptry marker, was reported for localization in the invasive stage of the malaria parasite including sporozoite and merozoite, the invasive stages for hepatocytes and erythrocyte respectively. However, there are no reports for the expression of RON-2 in the liver stage. Therefore, we hypothesized that RON-2 which was found to be involved in the invasion process would be expressed in liver stage parasites and would be used as a marker for liver stage schizont and hypnozoite. Here, the human hepatocyte chimeric mice were infected with P. vivax sporozoites before collecting the infected liver tissue for examination using the immunofluorescent technique. The results showed that RON-2 was expressed at the apical end of P. vivax sporozoites and merozoites. However, RON-2 was localized in the surroundings of liver stage schizonts and hypnozoites, and co-localized with Up-regulation in infective sporozoites protein 4 (UIS-4), a well-known form of PVM protein. In conclusion, RON-2 localized at the PVM of the liver stages of schizont and hypnozoite, can be a novel marker for the identification of P. vivax liver stage schizont and hypnozoite. This could be beneficial for further investigation on the treatment and control of the relapse caused by vivax malaria.